2020
DOI: 10.3390/w12123483
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Index-Based Approach in Geospatial Techniques for the Mapping of Flood Hazard Areas: A Case of Cape Coast Metropolis in Ghana

Abstract: Floods remain one of the disasters that destroy properties, livelihoods, and in extreme situations, take lives. As a way of prevention, geospatial applications have been employed in many cities to map flood zones and predict floods. For a country such as Ghana, floods have been ranked as the second fatal disaster after epidemics leading to several kinds of research to resolve them. To date, the Cape Coast Metropolis (CCM) has received little attention in terms of research, though flood cases in the area contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Cape Coast Metropolis is found in the coastal savannah ecological zone, which is characterised by two distinct seasons (wet and dry) annually, with annual rainfall ranging between 90 and 110 mm. It is mostly humid (relative humidity ranging from 60% to 80%) due to its proximity to the sea, with temperatures ranging between 24°C and 32°C (Danso et al, 2020). The metropolis stretches 13 km along the central coast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cape Coast Metropolis is found in the coastal savannah ecological zone, which is characterised by two distinct seasons (wet and dry) annually, with annual rainfall ranging between 90 and 110 mm. It is mostly humid (relative humidity ranging from 60% to 80%) due to its proximity to the sea, with temperatures ranging between 24°C and 32°C (Danso et al, 2020). The metropolis stretches 13 km along the central coast.…”
Section: Methodsmentioning
confidence: 99%
“…It currently has an estimated 189,925 people according to the 2021 population and housing census. Previous studies suggest its population grows at an annual rate of 3.1% (Danso et al, 2020). The metropolis is rapidly expanding to accommodate the increasing population and associated socio-economic activities.…”
Section: Study Contextmentioning
confidence: 99%
“…In this study, morphometric characteristics of KLCRS landscape, like elevation, slope, aspect, flow direction, stream network and order, and stream density, were modelled with the help of the Spatial Analyst tools in ArcGIS [26,45,46]. The Fill tool in ArcGIS was used to create depressionless DEM to prevent any interruption of continuous flow paths [46]. Using the inbuilt D8 method in the Spatial Analyst tool, the flow direction of KLCRS was modelled out of the fill DEM.…”
Section: Morphometric Analysismentioning
confidence: 99%
“…The flow direction was used as an input material to create a flow accumulation raster image. Following the procedures described in [46,47], the watershed was delineated, and stream network and stream density maps of KLCRS were produced. Based on Strahler's system of stream order [45,48] as a built-in tool in QGIS version 3.16, six stream orders of the study area were revealed.…”
Section: Morphometric Analysismentioning
confidence: 99%
“…Over the past few decades, remote sensing has played a crucial role in monitoring floods, and it has also solved the challenges related to the availability of data (Sharma et al 2018;Wang and Xie 2018;Rong et al 2020). In recent times, GIS has been widely used in vulnerability and risk assessment studies as a decision support system for its database and analytical ability (Lyu et al 2018;Choubin et al 2019;Danso et al 2020). Armenakis et al (2017) developed a flood risk map for the Don River watershed, Toronto, using high spatial resolution data and incorporated demographic indicators to enhance mitigation and preparedness planning.…”
Section: Introductionmentioning
confidence: 99%